Design of Civil Servant Data Management System at The National And Political Unit Agency at The Office of The Governor of West Papua Province - Siti Nur Asia; Sofyan Sofyan; Khaidil Khaidil (Indonesian Journal of Innovation Multidisipliner Research, 2023)
This research is motivated by the processing of employee data that has not been neatly arranged in a database, but in processing data it takes more time so it is not effective and efficient. This study uses a qualitative descriptive type of research using data collection methods, namely interviews, observations and literature studies. This application uses black box testing, PHP and MYSQL programming languages. The result of this research is to design a web-based civil servant data management system. The results of this study are in order to make it easier for employees, leaders to access information and the field of personnel in managing employee data so as to minimize time.